Influenciadoras digitais da região tocantina: um olhar sobre as peculiaridades e engajamento de conteúdos no instagram - MARINHO, Camila Silva (2021)
Given the power of influence achieved by digital influencers on the internet, especially on the social network Instagram, this research uses concepts of authors who discuss the Theory of Medium (MCLUHAN, 1964; MEYROWITZ, 1993; INNIS, 1949), social networks on the internet (RECUERO, 2009) and the characteristics of influencers (KARHAWI, 2019). The central objective is to investigate the peculiarities of the content published by the five main digital influencers of the Tocantina Region on Instagram, in addition to categorizing the themes and identifying which of them generate more engagement on the network. This is a quantitative descriptive field research of exploratory nature. Through an initial empirical survey the main profiles were filtered. For seven days the types of content published by them and the interaction of followers were observed. The results showed that although most of the posts are intended to promote brands, products, or services, the personal posts, in which the influencers appear showing moments of their daily lives, have high engagement rates. Even so, not all the influencers researched make use of this type of strategy.